Issues of Effective Agricultural Land Utilization and Land Tenure Organizationin Conditions of Lori Marz - Yeghiazaryan, G. M.; Efendyan, P. S.; Tovmasyan, L. G. (ՀԱԱՀ հիմնադրամ)
Based on the contemporary requirements for the development of effective ways for agricultural land utilization, a comprehensive analysis of land utilization planning and cadastral land evaluation was carried out by the example of Lori region. Results of the analysis of cadastral land evaluation and actual land use indices have disclosed the uncultivated land areas and their consecutive economic damage size caused to the community per agricultural land types. Based on the analysis, the coefficient values for identifying the conventional areas of the community land types have been derived which can make the evaluation process of land utilization measurable and comparable.
Keywords: Agricultural Engineering